RIGHTS OF NATURE: THE ECUADORIAN CASE - Echeverría, Hugo (Revista Esmat, 2017)
The recognition of rights to nature by the Constitution of Ecuador sets a new normative scenario for analysis of the role of law in human-nature interactions. Given the scope of such a recognition, one relying on unorthodox biocentric views, these rights raise controversy. To some, nature rights are rather symbolic; to others, these rights are not only real but fundamental to effectively address the ever-growing degradation of nature. Yet, others focus on enforcement and juridical interpretation of their normative content as to determine whether recognition of constitutional rights to nature provide the foundations for a more effective role of the law in this field.